DISTRIBUTION OF BOTTOM SEDIMENT BEFORE AND AFTER RECLAMATION AT CENTER POINT OF INDONESIA (CPI) MAKASSAR CITY - Maulana, Firly; Muhiddin, Amir Hamzah; Lanuru, Mahatma; Samad, Wasir; Ukkas, Marzuki (Jurnal Ilmu Kelautan SPERMONDE, 2023)
Characteristics and distribution of bottom sediment is one of the important parameters in determining the management plan and land use in coastal areas. The purpose of this study was to determine the condition of the distribution of bottom sediments and to compare the changes that occurred in the distribution of bottom sediment before and after the reclamation of the Center Point of Indonesia (CPI) in Makassar City. Sediment sampling was carried out using a grab sampler at four stations, namely stastions on the island adjacent to the reclamation area and two other stations in the water around the reclamation area. The results showed that the bottom sediment in the waters around the reclamation area consisted of coarse sand and medium sand with an organic matter content of 14.92% in the sediment. On the islands adjacent to the reclamation area, the bottom sediments are move varied, consisting of coarse sand, medium sand and fine sand with lower organic matter content of 4.92% to 5.38%.